Isopiestic osmotic coefficients of tetra-n-methylammonium chloride with guanidinium salts at 298.15 k - Kumar, Anil (Journal of Solution Chemistry, 2007)
Isopiestic osmotic coefficients are presented for aqueous mixtures of tetra-n-methylammonium chloride, (CH3)(4)NCl, with guanidinium salts such as GnCl, CH(3)COOGn, GnNO(3), GnClO(4) and Gn(2)SO(4) at 298.15 K up to an ionic strength of 2 mol center dot kg(-1). The osmotic coefficients are analyzed in terms of the Scatchard-Rush-Johnson equations. The activity coefficients of each electrolyte in the mixtures were calculated and fitted by the Harned-type equations. The molar excess Gibbs energy of mixing, Delta(m) G(E), of the mixtures were analyzed with Friedman's equations.
Keywords: aqueous solutions; isopiestic method; Osmotic coefficients; Scatchard-Rush-Johnson equations; tetramethylammonium salts